Doctorateness in Design Disciplines. Negotiating Connoisseurship and Criticism in Practice-related Fields - Nilsson, Fredrik; Dunin-Woyseth, Halina (FormAkademisk, 2013)
Discussions on the concept of ‘doctorateness’ have been growing during last years in traditional academic disciplines as well as in creative fields. This paper is a brief report from the first stage of a research project which studies how the concept of ‘doctorateness’ could be considered in the field of architecture, design and arts. The project builds upon a series of doctoral courses for architects and designers, and includes the study and evaluation of already accepted doctoral theses. In analyses of assessment assignments, the ‘connoisseurship model’ of Elliot W. Eisner was found to be useful. Eisner’s model of Connoisseurship & Criticism has served as the main tool for the analyses of empirical data, and as a framework for developing the concept of ‘doctorateness’ further. From the first phase of studies in the research project, the importance of particular kinds of awareness can be stressed as crucial for ‘doctorateness’, and here the model of connoisseurship and criticism has been operative. A more elaborate definition of ‘doctorateness’ is presumed to be of use as a pedagogical tool in research education in design fields as well as in dialogues between professionals of design practice and research.